Scattered information architecture: dealing with cyclical risks of split in corporate websites - Saorín, Tomás (Anuario ThinkEPI, 2012)
The tensions between centralization and decentralization in complex enterprise web sites are addressed from the perspective of conventional information architecture, based on the "islands of information" metaphor used by Rosenfeld and Morville. The needs include the identification and shaping of information spaces, the ability to manage multiple autonomous websites consistently, and a deeper knowledge of enterprise information architecture methodologies.
Keywords: Information architecture; Decentralization; Enterprise portals; Information integration; Enterprise information architecture.